GE_GERICHTE P/12113/2018 vom 14. September 2020 - GE Cour de justice (2020)
DENI DE JUSTICE;ASSISTANCE JUDICIAIRE;CLASSEMENT;NOTIFICATION;DOMICILE EN SUISSE;DOMICILE ÉLU;RESTITUTION DU DÉLAI | CPP.87; CPP.85; CPP.88; CPP.94